(untitled) (Romano džaniben, 2007)
Ľudovít Didi / Príbehy svätené vetrom Gejza Horváth / Trispras Ronald Lee / Learn Romani. Das-dúma Rromanes Vlado Oláh / Khamutno kamiben Nina Pavelčíková / Romové v českých zemích v letech 1945–1989 Jozef Ravasz / Identita Rómov na Žitnom ostrove Yvonne Slee / Torn Away, Forever Jsme přeci lidé, ne? – We’re all people, no? Peter Vermeersch / The Romani Movement. Minority Politics and Ethnic Mobilisation in Contemporary Europe Writers Festival India – 2006 (21-24 March 2006)